Determinan Kepatuhan Penerapan Protokol Kesehatan Dalam Upaya Pencegahan Penularan COVID-19 di Pasar Tradisional Ciputat Kota Tangerang Selatan - Manggala Yudha, Agung; Ramadhan, Gaung Eka (STIKES Ngesti Waluyo, 2023)
Coronavirus is a non-segmented, single-stranded positive-strand RNA virus. Corona viruses are included in the order Nidovirales, family Coronaviridae, and sub-family Orthocoronavirinae, which are divided into groups (surnames) α, β, γ, and δ according to their serotypic and genomic characteristics. Coronavirus is included in the Coronavirus genus of the Coronaviridae family. It is named after the protrusion in the form of a wreath on a viral envelope. The study aims to examine the determining factors of compliance with the implementation of health protocols as an effort to prevent COVID-19 transmission in Ciputat Traditional Market, South Tangerang City. The research methodology used in the research was quantitative method with cross sectional design. This research was conducted in July-August 2020 with 77 samples. The sampling technique was random sampling. Data analysis used univariate and bivariate analysis with chi-square test. The results of the analysis showed that there was a significant relationship between knowledge and compliance with the implementation of health protocols in preventing transmission of COVID-19 with a p-value 0.002; and also between Perceived Susceptibility (p value=0.002), Perceived Severity (p value=0.003), Perception of Barriers (p-value=0.005) with the compliance of health protocols implementation. This research is expected to be an input for the South Tangerang City Health Office in taking strategic step to prevent the transmission of COVID-19 at the Ciputat Traditional Market, South Tangerang City.